Critical Rationalist Traditions: Some Reflections - Dr. Faizal N Muhammad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Truth is difficult to get. It requires to be innovative to criticizing old theories and for inventing new theories. It is often so not only within sciences, but in all areas of knowledge. Genuine critical discussions are always difficult as irrational human interventions and private interferences will always be there. Any critical debate to be successful, it must be able to clarify even the slightest problem and even little contribution put forward for clear and precise understanding of the individual position as well of the opponent is very much essential. Rational and critical discussion may be occasional, while it may not aim at conversion but may cause further expectations.